Pendampingan dan Pelatihan Pengembangan Potensi Diri melalui Keterampilan Komunikasi dan Perencanaan Masa Depan di Yayasan Al Falah At Tirmidzi - Alfanur, Farah; Murti, Yusza Reditya; Alfaiza, Salsabila Aisyah (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Effective communication skills and mature future planning are essential competencies for individuals facing educational and professional worlds. However, many students still experience difficulties in developing their self-potential due to inadequate communication skills and limited understanding of future planning. To address these issues, the Training and Mentoring Program for Self-Potential Development Strategies with Communication Skills Techniques and Future Planning was designed to equip students with the necessary skills to become more confident and have clear future direction. This community service program was implemented at Yayasan Al Falah At Tirmidzi Ciganitri using practice-based training methods and intensive mentoring. The main activities included communication skills training, public speaking techniques, self-potential development, and career planning through career roadmap development. The approaches used encompassed interactive methods, simulations, group discussions, and individual mentoring to ensure participants could apply the knowledge gained in real life. The results of this program are expected to improve participants' communication abilities, both in expressing opinions effectively and in public speaking. Additionally, participants are better able to identify their interests and talents and develop more focused educational and future plans. Thus, this program not only provides short-term benefits but also contributes to building participants' independence and readiness in facing future challenges.